Estudos agronômicos e genômicos de manihot esculenta crantz: diversidade, correlação entre caracteres e número mínimo de SNPs. - Noia, Luina Ribeiro (2023)
Cassava is a food security crop with wide genetic diversity available for research in plant breeding. In this work, the genetic diversity of a cassava population consisting of 87 genotypes cultivated by small producers in the State of Espírito Santo was evaluated using SNPs, quantitative and qualitative traits. The correlation between traits and markers and the minimum number of SNPs required for the analyzes was also verified. The genetic parameters observed (Ho) and expected (He) heterozygosity, polymorphic information content (PIC) and fixation index (Fi) were calculated with the SNPs, which means were 0.46; 0.35;0,28; and - 0.34, respectively. Heterozygosity and PIC values can be considered high given the biallelic nature of the markers and the values reported by other authors. Ho values greater than He and negative Fi indicate a high number of heterozygotes. The quantitative traits were evaluated using the mixed model methodology (REML/BLUP) and heritabilities of 0.79, 0.55, 0.62 and 0.63 were observed for Height of the Aerial Part (HPA), Number of Total Roots (NRT), Weight of Total Roots (PESORT) and Commercial Roots (PESORC), respectively. Fourteen qualitative traits were also evaluated, including morphological descriptors of roots and aerial part, cooking time and presence of disease, of which the most variable were central lobe shape, petiole color and external stem color. The genotypes with the highest PESORT had white flesh and cooking time between zero and 20 min. The dendrograms based on SNPs, quantitative and qualitative traits formed 17, 9 and 10 groups and showed different composition, with the exception of some genotypes that showed similarity in the clusters regarding quantitative and SNPs data. The correlation was significant between fifteen pairs of characters, highlighting the correlation between SNPs with NRT and PESORT. Sets with 4, 15 and 50 SNPs were selected by resampling techniques, and distance matrices computed with these sets presented correlation between 0.4 and 0.56 with NRT and PESORT. The sets with four SNPs allowed to differentiate the genotypes according to the NRT and PESORT values. The analysis of the minimum number of SNPs demonstrated that few SNPs are necessary to calculate of genetic parameters, and it is possible to recover the values with only 50 SNPs if a confidence interval of 95% is considered. To obtain dendrograms with the same groups formed with all SNPs, a greater number of markers is required, 3000 for the cassava population. This value can be calculated by resampling and distance matrix correlation techniques, considering a correlation value of 0.99. The analyzes characterized important tools for cassava breeding, among them, a population with sufficient molecular, morphological and productive diversity for the selection of genotypes with agronomic characteristics of interest; SNPs with correlation with the main productivity traits that can be studied for marker-assisted selection; and the minimum number of SNPs to evaluate genetic diversity in the population.